The IgG2 Isotype of Anti–Transcription Intermediary Factor 1γ Autoantibodies Is a Biomarker of Cancer and Mortality in Adult Dermatomyositis. Issue 8 (8th July 2019) - Aussy, Audrey; Fréret, Manuel; Gallay, Laure; Bessis, Didier; Vincent, Thierry; Jullien, Denis; Drouot, Laurent; Jouen, Fabienne; Joly, Pascal; Marie, Isabelle; Meyer, Alain; Sibilia, Jean; et al.
Abstract : Objective: Anti–transcription intermediary factor 1γ (anti‐TIF1γ) antibodies are the main predictors of cancer in dermatomyositis (DM). Yet, a substantial proportion of anti‐TIF1γ–positive DM patients do not develop cancer. This study was undertaken to identify biomarkers to better evaluate the risk of cancer and mortality in DM. Methods: This multicenter study was conducted in adult anti‐TIF1γ–positive DM patients from August 2013 to August 2017. Anti‐TIF1γ autoantibody levels and IgG subclasses were identified using a newly developed quantitative immunoassay. Age, sex, DM signs and activity, malignancy, and creatine kinase (CK) level were recorded. Risk factors were determined by univariate and multivariate analysis according to a Cox proportional hazards regression model. Results: Among the 51 adult patients enrolled (mean ± SD age 61 ± 17 years; ratio of men to women 0.65), 40 (78%) had cancer and 21 (41%) died, with a mean ± SD survival time of 10 ± 6 months. Detection of anti‐TIF1γ IgG2 was significantly associated with mortality ( P = 0.0011) and occurrence of cancer during follow‐up ( P < 0.0001), with a 100% positive predictive value for cancer when the mean fluorescence intensity of anti‐TIF1γ IgG2 was >385. None of the patients developed cancer after 24 months of follow‐up. Univariate survival analyses showed that mortality was also associated with age >60 years ( P = 0.0003), active DM ( P = 0.0042), cancer ( P = 0.0031), male sex ( P = 0.011), and CK level >1, 084 units/liter ( P = 0.005). Multivariate analysis revealed that age >60 years ( P = 0.015) and the presence of anti‐TIF1γ IgG2 ( P = 0.048) were independently associated with mortality. Conclusion: Our findings indicate that anti‐TIF1γ IgG2 is a potential new biomarker of cancer that should be helpful in identifying the risk of mortality in anti‐TIF1γ–positive DM patients.